1996
DOI: 10.21273/jashs.121.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matric and Osmotic Priming Treatments on Broccoli Seed Germination

Abstract: Priming, a controlled-hydration treatment followed by redrying, improves the germination and emergence of seeds from many species. We compared osmotic and matric priming to determine which was the most effective treatment for improving broccoli seed germination and to gain a greater understanding of how seed vigor is enhanced by priming. Broccoli (Brassica oleracea L. var. italica) seeds were osmotically primed in polyethylene glycol (PEG 8000) at -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Seed priming techniques have been used to reduce the emergence time, to get synchronized emergence, to improve emergence rate, and to have better seedling stand in many horticultural (Rudrapal and Nakamura 1998;Bradford et al 1990;Khan 1992;Jett et al 1996) and field crops such as wheat, maize (Dell'Aquilla and Tritto 1990;Chowdhary and Baset 1994;Basra et al 2002) and more recently rice Kim 1999, 2000;Basra et al 2003Basra et al , 2004Basra et al , 2005Farooq et al 2004Farooq et al , 2005bFarooq et al , 2006a. These invigoration techniques include hydropriming, osmoconditioning, osmohardening, hardening, and ascorbate priming.…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming techniques have been used to reduce the emergence time, to get synchronized emergence, to improve emergence rate, and to have better seedling stand in many horticultural (Rudrapal and Nakamura 1998;Bradford et al 1990;Khan 1992;Jett et al 1996) and field crops such as wheat, maize (Dell'Aquilla and Tritto 1990;Chowdhary and Baset 1994;Basra et al 2002) and more recently rice Kim 1999, 2000;Basra et al 2003Basra et al , 2004Basra et al , 2005Farooq et al 2004Farooq et al , 2005bFarooq et al , 2006a. These invigoration techniques include hydropriming, osmoconditioning, osmohardening, hardening, and ascorbate priming.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated such germination at osmotic potentials of – 0.5 bar (Frett and Pill 1989) and as promptly as 96 h after initial treatment (Jones and Sanders 1987). Jett et al. (1996) established that the optimum enhancement of primed seeds would occur just below the osmotic potential threshold for their germination, with enhancement at or above this threshold causing premature radicle protrusion, while Mauromicale and Cavallaro (1995) suggested a cultivar‐dependent response.…”
Section: Introductionmentioning
confidence: 99%
“…Beckman et al (1993) reported that solid matrix priming significantly increased adventitious roots than that of control in switch grass during green house experiment. Jett et al (1996) also reported that root growth rates of matricprimed seeds were significantly higher than either osmotic or non-primed seedlings at most temperatures. The increase in root/shoot ratio with hydropriming treatments may be due to the fact that, priming induced nuclear replication in root tips of fresh seeds.…”
Section: Resultsmentioning
confidence: 87%